Skin Protective Activity of Silymarin and its Flavonolignans - Vostálová, Jitka; Tinková, Eva; Biedermann, David; Kosina, Pavel; Ulrichová, Jitka; Rajnochová Svobodová, Alena (Molecules (Basel, Switzerland), 2019)
Silybum marianum (L.) is a medicinal plant traditionally used in treatment of liver disorders. In last decades, silymarin (SM), a standardized extract from S. marianum seeds has been studied for its dermatological application, namely for UVB-protective properties. However, information on SM and its polyphenols effect on activity of enzymes participating in the (photo)aging process is limited. Therefore, evaluation of SM and its flavonolignans potential to inhibit collagenase, elastase, and hyaluronidase in tube tests was the goal of this study. The antioxidant and UV screening properties of SM and its flavonolignans silybin, isosilybin, silydianin, silychristin and 2,3-dehydrosilybin (DHSB) were also evaluated by a DPPH assay and spectrophotometrical measurement. DHSB showed the highest ability to scavenge DPPH radical and also revealed the highest UVA protection factor (PF-UVA) that corresponds with its absorption spectrum. SM and studied flavonolignans were found to exhibit anti-collagenase and anti-elastase activity. The most potent flavonolignan was DHSB. None of studied flavonolignans or SM showed anti-hyaluronidase activity. Our results suggest that SM and its flavonolignans may be useful agents for skin protection against the harmful effects of full-spectrum solar radiation including slowing down skin (photo)aging.
Keywords: semena rostlinná; Silymarin; antioxidancia; elastase; collagenase; rostlinné extrakty; kůže; Seeds; ostropestřec mariánský; silymarin; ultrafialové záření; sun protection factor; Plant Extracts; lidé; Antioxidants; Skin; Humans; Ultraviolet Rays; Flavonolignans; Silybum marianum; flavonolignany